Ekualisasi Biaya Gaji Pada SPT Tahunan Badan Dengan SPT Masa PPh Pasal 21 Pada ZAD Konsultama (Studi Kasus PT XXX) - Riri Rumaizha; Ayu Nuroktapiani (LPPM POLITEKNIK LP3I BANDUNG, 2026)
The objective of this study is to ascertain the manner in which the tax equalisation process functions in regard to the discrepancy arising from the calculation of income tax Article 21 salary costs and the reporting of Income Tax Return Article 21. The discrepancy in question gave rise to the issuance of a Request for Explanation of Data and/or Information (SP2DK) to PT.XXX, a client of ZAD Konsultama. The research method employed is a quantitative descriptive method, which involves the explanation of data through description or explanation. This method is based on the results of observations, documentation, and interviews. The data employed by the author in conducting research on tax equalisation is sourced from the Annual Corporate Tax Return and Monthly Income Tax Return, Article 21 at PT XXX, for the 2020 tax year. Following a period of research and discussion, the author arrived at the conclusion that there was a discrepancy in salary costs amounting to IDR 626,500,000. This was attributed to the non-reporting of salaries from April to December, a failure attributable to the client's inadequate comprehension of the Income Tax Article 21 incentive, a measure implemented by the government.